EFFECT OF CYBERPEDAGOGY ON INCREASE OF EDUCATIONAL EFFICIENCY IN EARLY DEVELOPMENT PERIODS AND TODAY. (Scientific journal of the Fergana State University, 2024)
This article examines the early development of cyber pedagogy from the 1960s to 2000 and current research in the digital learning environment, which helps students learn new technologies, search and analyze data, learn online, and more. providing opportunities for cooperation, current problems in cyber pedagogy, i.e. the use of technologies, teachers' readiness, the order of education, the joint use of practical and theoretical knowledge and ways to solve these problems, written by scientists who contributed to the development of cyber pedagogy the literature is analyzed, these books are written for students, teachers and scientists who want to develop specialization in the field of technology, the reforms in the field of cyber-pedagogy in Uzbekistan and the world in order to increase the effectiveness of education, as well as the interactive methods used in the educational process in the digital age educational platforms, integrated learning, mastering, collaborative learning, data analytics and methods to ensure innovation and development in the field of cyberpedagogy are covered. The development of cyber pedagogy gives students an understanding of the technologies used, teaches them how to help them work with information and receive education. Cyber-pedagogy increases the impact of education in the digital age and is of great importance in making the learning processes of students more effective and stimulating learning.